1997
DOI: 10.1084/jem.186.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Interferon γ (IFN-γ) Is Necessary for the Genesis of Acetylcholine Receptor–induced Clinical Experimental Autoimmune Myasthenia gravis in Mice

Abstract: Experimental autoimmune myasthenia gravis (EAMG) is an animal model of human myasthenia gravis (MG). In mice, EAMG is induced by immunization with Torpedo californica acetylcholine receptor (AChR) in complete Freund's adjuvant (CFA). However, the role of cytokines in the pathogenesis of EAMG is not clear. Because EAMG is an antibody-mediated disease, it is of the prevailing notion that Th2 but not Th1 cytokines play a role in the pathogenesis of this disease. To test the hypothesis that the Th1 cytokine, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
3
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 44 publications
0
116
3
2
Order By: Relevance
“…The suppressive effect of anti-CD40L Ab in suppression of ongoing chronic EAMG in our study was associated with down-regulation of the pathogenic inflammatory cytokine IFN-␥ and of IL-12 ( Fig. 2), both of which have been previously demonstrated to be directly or indirectly involved in induction of EAMG (31)(32)(33)(34)(35). The selective suppressive effect on Th1-type differentiation by anti-CD40L treatment is consistent with models of other autoimmune diseases such as multiple sclerosis, diabetes, and thyroiditis (17,18,36,37), and with graft-vshost disease and graft rejection (38,39).…”
Section: Figure 3 Effect Of Anti-cd40l Treatment On Costimulatory Famentioning
confidence: 77%
“…The suppressive effect of anti-CD40L Ab in suppression of ongoing chronic EAMG in our study was associated with down-regulation of the pathogenic inflammatory cytokine IFN-␥ and of IL-12 ( Fig. 2), both of which have been previously demonstrated to be directly or indirectly involved in induction of EAMG (31)(32)(33)(34)(35). The selective suppressive effect on Th1-type differentiation by anti-CD40L treatment is consistent with models of other autoimmune diseases such as multiple sclerosis, diabetes, and thyroiditis (17,18,36,37), and with graft-vshost disease and graft rejection (38,39).…”
Section: Figure 3 Effect Of Anti-cd40l Treatment On Costimulatory Famentioning
confidence: 77%
“…Although earlier work had indicated that ectopic expression of IFN-c at the neuromuscular junction provoked MG-like disease [33], our current understanding of the role of IFN-c in EAMG is far from conclusive. For example, mice deficient of IFN-c [25] or IFN-c receptor [26] are resistant to EAMG, yet some groups have shown that IFN-c deficiency may not significantly alter the course of disease [27,34]. Thus, while Th1 responses may possibly play a role in the disease depending on the experimental system used, the question arises on whether other inflammatory cytokine(s) with potent propathogenic effects, such as IL-17, are required for the expression of EAMG.…”
Section: Discussionmentioning
confidence: 99%
“…We and others [25][26][27] have previously found that the development of EAMG is not dramatically altered by IFN-c deficiency. To investigate whether the effects of IL-17 on EAMG were related to or depended on IFN-c, we treated IFN-c -/-mice with IL-17 during EAMG induction, using the same regimen used for the B6 mice.…”
Section: Il-17 Facilitates Autoantibody Responses and Clinical Eamg Imentioning
confidence: 93%
“…However, IFN-g is still a controversial factor in the pathogenesis of EAMG. B6 Mice with IFN-g or IFN-gR deficiency are less susceptible to EAMG [25,30]. On the contrary, IFN-gdeficient B6 mice developed EAMG with a frequency similar to Spleen and lymph node MNC were obtained from rats receiving TGF-b1-DC, naïve DC or PBS on day 39 p.i.…”
Section: Discussionmentioning
confidence: 99%